The nature and norms of scientific explanation: Some preliminaries - Peña, Abel; Wright, Cory (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2023)
There are at least two deep and related debates about explanation: about its nature and about its norms. The aim of this special issue of Philosophical Problems in Science/Zagadnienia Filozoficzne w Nauce (ZFN) is to survey whether or not a consensus is at hand in these debates and to help settle what it can. The overarching foci are twofold: (i) the nature of scientific explanation, with special attention to the debate between ontic and epistemic conception of explanation, and (ii) the norms of scientific explanation, with special attention to so-called ‘ontic’ (or better, ‘alethic’) norms like truth and referential success and epistemic norms like intelligibility and idealized understanding. It called for advocates of various conceptions to articulate the current state of these debates. Researchers and scholars from around the globe—including Poland, Canada, Korea, The Netherlands, the United States, Greece, Austria, and Belgium—contributed. The special issue also attempts to provide an opening for new work on the norms of explanation, such as truth or model-based accuracy, information compression, abstraction, and generalization.